1987
DOI: 10.1002/j.2161-1920.1987.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

A Common Sense Approach: Fighting Poverty Among Single‐Parent Families

Abstract: The author reviews current trends, predictions, and statistics concerning single‐parent families living in poverty and provides a common sense approach for support groups and networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The systematic employment of four methods for changing self-efficacy resulted in significant changes in participants' financial independence self-efficacy over a relatively short time.It has been predicted that by the year 2000 the majority of those falling below the poverty level will be women and their dependent children (Hewlett, 1986). Even now women are the heads of the majority of families with children that fall below the poverty level (Bradley, 1987). There are several factors that contribute to women and their children constituting the majority of those below the poverty level.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic employment of four methods for changing self-efficacy resulted in significant changes in participants' financial independence self-efficacy over a relatively short time.It has been predicted that by the year 2000 the majority of those falling below the poverty level will be women and their dependent children (Hewlett, 1986). Even now women are the heads of the majority of families with children that fall below the poverty level (Bradley, 1987). There are several factors that contribute to women and their children constituting the majority of those below the poverty level.…”
mentioning
confidence: 99%
“…One simple factor is the earning power of a family with only one adult wage earner. It has been found that women experience a significant reduction in financial stability as a consequence of divorce (Bradley, 1987).The problems that women who are heads of households face in terms of self-sufficiency and independence are numerous. Wood (1989) suggested that motivation is impaired when women perceive that their efforts at obtaining employment are futile and they subsequently do not attempt to get into the job market.…”
mentioning
confidence: 99%
See 1 more Smart Citation